2004
DOI: 10.1038/sj.bjc.6601815
|View full text |Cite
|
Sign up to set email alerts
|

Cost study of metal stent placement vs single-dose brachytherapy in the palliative treatment of oesophageal cancer

Abstract: Self-expanding metal stent placement and single-dose brachytherapy are commonly used for the palliation of oesophageal obstruction due to inoperable oesophagogastric cancer. We randomised 209 patients to the placement of an Ultraflex stent (n ¼ 108) or single-dose brachytherapy (12 Gy, n ¼ 101). Cost comparisons included comprehensive data of hospital costs, diagnostic interventions and extramural care. We acquired detailed information on health care consumption from a case record form and from monthly home vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 30 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…We used two primary data sources: 1) hospital discharge registers (HDR) with full national coverage to estimate the hospitalization rate and 2) emergency-department (ED) surveillance systems for the incidence of non-admitted ED patients[10,11]. Since ED systems did not have nationwide coverage, country-specific extrapolation factors were used to extrapolate the ED incidence towards national level for the respective types of injury by country[7,11]. We computed YLL using a standard life table[5,12].…”
Section: Methodsmentioning
confidence: 99%
“…We used two primary data sources: 1) hospital discharge registers (HDR) with full national coverage to estimate the hospitalization rate and 2) emergency-department (ED) surveillance systems for the incidence of non-admitted ED patients[10,11]. Since ED systems did not have nationwide coverage, country-specific extrapolation factors were used to extrapolate the ED incidence towards national level for the respective types of injury by country[7,11]. We computed YLL using a standard life table[5,12].…”
Section: Methodsmentioning
confidence: 99%
“…The cost of stenting with that of single-dose brachytherapy has been prospectively compared by polinder et al [118]. They demonstrated that the cost of each treatment is similar.…”
Section: Fistulaementioning
confidence: 98%
“…This study was performed alongside a cohort of patients with unresectable EC, but the short follow-up (2 months) probably failed to capture most of the adverse events associated with the palliative treatments under evaluation. Polinder et al performed a cost-analysis on a large randomized trial comparing esophageal metal stent to single dose brachytherapy [31]. While procedure-related costs were higher in the stent group, post-treatment care was more expensive in patients managed with brachytherapy, which accounted for similar total costs.…”
Section: Discussionmentioning
confidence: 97%